Religious nationalism and negotiation : Islamic identity and the resolution of the Israel/Palestine conflic - De Villiers, Shirley (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2004)
The use of violence in the Israel/Palestine conflict has been justified and legitimised by an appeal to religion. Militant Islamist organisations like Ramas have become central players in the Palestinian political landscape as a result of the popular support that they enjoy. This thesis aims to investigate the reasons for this support by analysing the Israel/Palestine conflict in terms of Ruman Needs Theory. According to this Theory, humans have essential needs that need to be fulfilled in order to ensure survival and development. Among these needs, the need for identity and recognition of identity is of vital importance. This thesis thus explores the concept of identity as a need, and investigates this need as it relates to inter-group conflict. In situating this theory in the Israel/Palestine conflict, the study exammes how organisations like Ramas have Islamised Palestinian national identity in order to garner political support. The central contention, then, is that the primary identity group of the Palestinian population is no longer nationalist, but Islamic/nationalist. In Islamising the conflict with Israel as well as Palestinian identity, Ramas has been able to justify its often indiscriminate use of violence by appealing to religion. The conflict is thus perceived to be one between two absolutes - that of Islam versus Judaism. In considering the conflict as one of identities struggling for survival in a climate of perceived threat, any attempt at resolution of the conflict needs to include a focus on needs-based issues. The problem-solving approach to negotiation allows for parties to consider issues of identity, recognition and security needs, and thus ensures that the root causes of conflicts are addressed, The contention is that this approach is vital to any conflict resolution strategy where identity needs are at stake, and it provides the grounding for the success of more traditional zero-sum bargaining methods. A recognition of Islamic identity in negotiation processes in Israel/Palestine may thus make for a more comprehensive conflict resolution strategy, and make the outcomes of negotiations more acceptable to the people of Palestine, thus undermining the acceptance of violence that exists at present.
Keywords: Arab-Israeli conflict; Palestinian Arabs -- Civil rights -- Israel; Nationalism -- Middle East; Religion and politics -- Middle East; Jewish-Arab relations; Nationalism -- Religious aspects -- Islam -- History -- 20th century